Evaluation of the recombinant egagb8/2 antigen for the diagnosis of cystic echinococcosis in tibetan sheep on the qinghai-tibetan plateau, china - Hong DUO; Yong FU; Xiuying SHEN; Zhihong GUO; Xueyong ZHANG; Yijuan MA; Mohammed YOSRI; Tiancong SUN; Youlu CHEN; Gengqiu JIUNAI (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
The unique geographical and ecological conditions of the Qinghai-Tibetan Plateau (QTP) constitute the environmental conditions of the natural foci of cystic echinococcosis (CE). It is a rare and highly endemic area in the world. The main host of the pathogen, Tibetan sheep, is widely distributed, and the population density is on the rise in recent years, which increases the pressure on the transmission and risk of the natural epidemic source. Currently, the developments of serological diagnosis test for Echinococcus granulosus infection on the QTP Tibetan sheep are scanty, which seriously restricts the epidemiological investigation of CE in Tibetan sheep on the QTP. EgAgB8/2 is one of the most important targets of host antibody response in CE and has better diagnostic performance in livestock. This study expressed the recombinant EgAgB8/2 antigen of E. granulosus from Tibetan sheep in prokaryotic expression vector, and also preliminarily evaluated its potential value for diagnosing CE in Tibetan sheep using indirect ELISA. Our preliminary results shown that the recombinant EgAgB8/2 antigen had good immunogenicity and exhibited high sensitivity (95%) and high specificity (100%) and no cross-reacted with both Taenia multiceps and Taenia hydatigena. Further studies are needed to collect more Tibetan sheep sera from E. granulosus and other parasitic infections, which may evaluate further sensitivity, specificity and cross-reactive of recombinant EgAgB8/2 antigen in Tibetan sheep positive for CE of the QTP, China.